Hierarchy, segregation, and impurity: political loyalty in traditionalist Salafism - Abdessamad Belhaj (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2026)
This article revisits the Salafi doctrine of al-walāʾ wal-barāʾ (loyalty and disavowal) as a moral and political foundation for constructing group identity, defining allegiance, and excluding others. Rather than treating loyalty and disavowal solely as theological categories, the article shifts the analysis toward their ethical and political implications. Using a qualitative textual approach and a discursive-historical method, it critically examines three traditionalist Salafi discourses on loyalty written by Ṣāliḥ al-Fawzān, Sayyid Saʿīd ʿAbd al-Ghanī, and Ma’mūn Ḥammūsh, representing Saudi Arabian, Egyptian, and Syrian contexts, respectively. The analysis shows that al-Fawzān promotes an exclusivist political theology of loyalty based on religious belonging, ʿAbd al-Ghanī emphasizes the distinction between legitimate and illegitimate loyalty through obedience to religious commands, while Ḥammūsh frames loyalty as an expression of religious and political purity. Across these discourses, legitimate loyalty is associated with orthodox belief, Islamic law, and moral sincerity, whereas illegitimate loyalty is linked to non-Muslims, heterodox Muslims, secular orders, and social relations perceived to compromise religious purity. The article argues that traditionalist Salafism constructs an exclusive, hierarchical, and purist group identity with potential implications for mistrust, segregation, and hostility toward Muslims and non-Muslims in pluralistic societies.